Lipoprotein lipids in older people. Results from the Cardiovascular Health Study. The CHS Collaborative Research Group. - Ettinger, W H; Wahl, P W; Kuller, L H; Bush, T L; Tracy, R P; Manolio, T A; Borhani, N O; Wong, N D; O'Leary, D H (Circulation, 1992)
BACKGROUND: Cardiovascular disease is the leading cause of death and disability in older people. There is little information about the distributions of risk factors in older populations. This article describes the distribution and correlates of lipoprotein lipids in people greater than or equal to 65 years old. METHODS AND RESULTS: Lipoprotein lipid concentrations were measured in 2,106 men (M) and 2,732 women (F) who were participants in the Cardiovascular Health Study, a population-based epidemiological study. Distributions of lipids by age and sex and bivariate and multivariate relations among lipids and other variables were determined in cross-sectional analyses. Mean concentrations of lipids were cholesterol: M, 5.20 +/- 0.93 mmol/l (201 +/- 36 mg/dl) and F, 5.81 +/- 0.98 mmol/l (225 +/- 38 mg/dl); triglyceride (TG): M, 1.58 +/- 0.85 mmol/l (140 +/- 75 mg/dl) and F, 1.57 +/- 0.78 mmol/l (139 +/- 69 mg/dl); high density lipoprotein cholesterol (HDL-C): M, 1.23 +/- 0.33 mmol/l (48 +/- 16 mg/dl), and F, 1.53 +/- 0.41 mmol/l (59 +/- 16 mg/dl); low density lipoprotein cholesterol (LDL-C): M, 3.27 +/- 0.85 mmol/l (127 +/- 33 mg/dl) and F, 3.57 +/- 0.93 mmol/l (138 +/- 36 mg/dl). The total cholesterol to HDL-C ratios were M, 4.49 +/- 1.29 and F, 4.05 +/- 1.22. TG, total cholesterol, and LDL-C concentrations were lower with increasing age, the last more evident in men than in women. TG concentration was positively associated with obesity (in women), central fat patterning, glucose intolerance, use of beta-blockers (in men), and use of estrogens (in women) and negatively associated with age, renal function, alcohol use, and socioeconomic status. In general, HDL-C had opposite relations with these variables, except that estrogen use was associated with higher HDL-C concentrations. LDL-C concentration was associated with far fewer variables than the other lipids but was negatively associated with age in men and women and positively correlated with obesity and central fat patterning and negatively correlated with renal function and estrogen use in women. There were no differences in total cholesterol and LDL-C concentrations among participants with and without prevalent coronary heart disease and stroke, but TG concentration was higher and HDL-C lower in men with both coronary heart disease and stroke and in women with coronary heart disease. CONCLUSIONS: Cholesterol and cholesterol/HDL-C ratio were lower and HDL-C higher than previously reported values in older people, suggesting that lipid risk profiles may be improving in older Americans. TG and HDL-C concentrations, and to a lesser extent LDL-C, were associated with potentially important modifiable factors such as obesity, glucose intolerance, renal function, and medication use.
Keywords: Aged; Aging; Cardiovascular Diseases; Cardiovascular Physiological Phenomena; Cholesterol, HDL; Cholesterol, LDL; Cross-Sectional Studies; Female; Health Status; Humans; Lipids; Lipoproteins; Male; Multivariate Analysis; Triglycerides